Efektivitas Edukasi Audio Visual terhadap Peningkatan Pengetahuan dan Sikap Remaja Putri tentang Gizi Seimbang “Isi Piringku” - Musdalipa Musdalipa; Fenti Putri Cahyani; Kristina Paskana; Nora Veronica; Lety Arlenti; Herianti Herianti (Malahayati Nursing Journal, 2026)
ABSTRACT Young women are the early period of contribution to intergenerational quality. Where adolescent girls with nutritional problems such as anemia, obesity and chronic energy deficiency (SEZ), if the adolescent girl is pregnant, the risk of giving birth to a baby with low birth weight (BBLR) and stunting, premature birth, and maternal and child mortality during childbirth is higher. One of the efforts that can be made through balanced nutrition health education. Education in this case is part of nutrition education as an effort to bring about changes in knowledge and attitudes in terms of consuming balanced nutritional foods in the visual of Isi Piringku. The visual of Fill My Plate depicts a healthy eating guide with 50% vegetables and the other 50% in the form of staples and side dishes. The use of audio-visual media in providing education because it is considered interesting and not noticeable by displaying movements, images and sounds. The purpose of this study was to determine the influence of audio visual intervention on the knowledge and attitudes of adolescent girls about balanced nutrition "fill my plate" at SMP Negeri 4 Kaur. The research design was quisy-experiment with a one group pretest – posttest design with a population of adolescent girls in grade IX of SMPN 4 Kaur. The sample in this study is 32 people. Sampling in this study used purposive sampling technique. The results of the analysis of this study using the Sample Paired T-test showed that there was an influence of audio visual intervention on the knowledge and attitude of adolescent girls about balanced nutrition "fill my plate" at SMP Negeri 4 Kaur. Keywords: Fill My Plate, Knowledge, Attitude, Audio Visual, Young Women.  ABSTRAK Remaja putri menjadi periode awal kontribusi terhadap kualitas antar generasi. Dimana remaja putri dengan masalah gizi seperti anemia, obesitas dan kekurangan energi kronik (KEK), jika remaja putri tersebut hamil, maka resiko melahirkan dengan bayi berat badan lahir rendah (BBLR) dan stunting, kelahiran prematur, serta kematian ibu dan anak saat melahirkan lebih tinggi. Salah satu upaya yang dapat dilakukan melalui edukasi kesehatan gizi seimbang. Edukasi dalam hal ini merupakan bagian dari pendidikan gizi sebagai upaya untuk mengadakan perubahan pengetahuan dan sikap dalam hal konsumsi makanan gizi seimbang dalam visual Isi Piringku. Visual Isi Piringku menggambarkan panduan makan sehat setiap sekali makan dengan 50% bagian sayuran dan sedangkan 50% lainnya berupa makanan pokok dan lauk pauk. Penggunaan media audio visual dalam pemberian edukasi karena dianggap menarik dan tidak menoton dengan menampilkan gerak, gambar dan suara. Tujuan penelitian ini untuk mengetahui pengaruh intervensi audio visual terhadap pengetahuan dan sikap remaja putri tentang gizi seimbang “isi piringku” di SMP Negeri 4 Kaur. Desain penelitian quisy-eksperimen dengan rancangan one group pretest – posttest dengan populasi remaja putri kelas IX SMPN 4 Kaur. Sampel dalam penelitian ini yaitu sebanyak 32 orang. Pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling. Hasil analisis penelitian ini menggunakan uji Sample Paired T-tes menunjukkan bahwa ada pengaruh intervensi audio visual terhadap pengetahuan dan sikap remaja putri tentang gizi seimbang “isi piringku” di SMP Negeri 4 Kaur. Kata Kunci: Isi Piringku, Pengetahuan, Sikap, Audio Visual, Remaja Putri.